2013
DOI: 10.1016/j.snb.2012.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal-based sensors for selective and quantitative detection of nitrogen dioxide

Abstract: A highly sensitive nitrogen dioxide (NO2) sensor based on orientational transition of a thin film of liquid crystal (LC) supported on a gold surface is reported. Transport of NO2 molecules through the LC film to the LC-gold interface induces an orientation transition in the LC film. The dynamic behavior of the sensor response exhibits a concentration-dependent response rate that is employed to generate an algorithm for quantitative determination of unknown concentrations. Sensitive, selective and reversible de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Additionally, several secondary factors play an equally important role to the interplay between VOCs and LCs, such as the roughness of the substrate, the chemical functionalities of the sensing material itself, the LC layer thickness, the transport efficiency of the analyte molecules to the LC/interface, and the adsorption–desorption kinetics at the LC‐interface. [ 46,47 ]…”
Section: Functional Liquid Crystal Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several secondary factors play an equally important role to the interplay between VOCs and LCs, such as the roughness of the substrate, the chemical functionalities of the sensing material itself, the LC layer thickness, the transport efficiency of the analyte molecules to the LC/interface, and the adsorption–desorption kinetics at the LC‐interface. [ 46,47 ]…”
Section: Functional Liquid Crystal Materialsmentioning
confidence: 99%
“…In this work, we focus on the prevailing interaction mechanisms of LC sensing systems with gas analytes, implementing solely thermotropic systems. We report on the sensing capabilities of platforms that exploit not only interfacial phenomena, [ 45–47 ] but also changes in the bulk, [ 43,44,48 ] yielding various measurable outputs. Furthermore, we detail the strategies in which LCs amplify or directly participate in the molecular recognition of gases and VOCs and we provide details on the probing approaches and transduction (this term refers to the ability of converting variations in physical properties such as brightness or electrical conductivity into a measurable signal) methods employed so far.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that cholesteric liquid crystals (CLCs) have great potential to be used as gas or environmental sensors . The peak wavelength of selective reflection (λ max ) of CLCs changes upon interaction with an adsorbed gas …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that cholesteric liquid crystals (CLCs) have great potential to be used as gas or environmental sensors. [3][4][5][6][7][8][9][10][11][12][13][14] The peak wavelength of selective reflection (λ max ) of CLCs changes upon interaction with an adsorbed gas. 15 Despite the many research studies conducted on CLCs, we found none that had investigated the relationship between the CLC chemical structures and the shift in λ max upon exposure to different VOCs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these materials have become good candidates for technologic application in electro-optic displays, in solar cells [6], as sensors [7], for high-density memory storage [8] and in light-emitting diodes (OLEDs) [9].…”
Section: Introductionmentioning
confidence: 99%